Studies of the intestinal metabolism of oral gold - Weisman, M H; Hardison, W G; Walz, D T (Journal of rheumatology, 1980)
In order to understand some of the unique toxic/therapeutic properties of the orally administered gold containing compound auranofin, the intestinal metabolism of gold was studied in 4 normal subjects. A triple lumen intestinal perfusion apparatus was used to measure intestinal flux using a non-absorbable radiolabelled marker dilution technique. Over a short (50 cm) segment of proximal small bowel, substantial disappearance of gold was observed; the findings, however, were most consistent with a loose, reversible adsorption onto the enteric cell surface rather than true trans-mucosal absorption. There was no evidence for an entero-hepatic recirculation of gold in these subjects or in 4 additional patients with rheumatoid arthritis studied in a similar manner.